Розміщення навісних машин на тракторному самохідному шасі з умов забезпечення стійкості машино-тракторного агрегату - Краснокутський, Володимир Миколайович (Національний технічний університет "Харківський політехнічний інститут", 2025)
Метою статті є аналіз умов забезпечення поздовжньої та поперечної стійкості машино-тракторних агрегатів (МТА) на базі тракторних самохідних шасі (ТША) при агрегатуванні з різними навісними машинами та обладнанням. Розглянуто критерії статичної й динамічної стійкості та вплив координат центру ваги навісного обладнання на безпечність функціонування МТА. Використано аналітичні та графічні методи визначення допустимих зон навішування. Отримані результати можуть бути застосовані під час проектування та компонування МТА.

The purpose of the article is to establish scientifically based conditions for ensuring longitudinal and transverse stability of aggregates based on self-propelled tractor chassis when mounting attachments of different weights and designs. The paper considers the relationship between the static and dynamic stability of the unit, as well as the factors that determine their change when working on ascents, slopes, and micro-relief irregularities. The influence of the coordinates of the center of gravity of the mounted machine, track width, chassis weight parameters, and the interaction of working bodies with the ground on the formation of stability reserves is analyzed. Analytical expressions and graphical dependencies are presented that allow determining the permissible vertical and horizontal coordinates of the center of gravity of the mounted machine based on the requirements for safe operation. It is shown that changing the configuration of the unit and the nature of the aggregation can both increase and decrease stability, which must be taken into account at the design and verification calculation stages. The recommendations provided can be used to optimize the layout of tractor self-propelled chassis, establish rational mounting areas, and determine the working track to ensure the reliability and stability of units in real operating conditions.
Placement of attached machines on a self-propelled tractor chassis to ensure the stability of the machine-tractor unit
Keywords: тракторні самохідні шасі; трактора; навісна машина; статична стійкість; динамічна стійкість; повздовжня стійкість; поперечна стійкість; запас стійкості; допустимі зони навішування; машино-тракторний агрегат; self-propelled tractor chassis; tractor; mounted machine; static stability; dynamic stability; longitudinal stability; transverse stability; stability margin; permissible mounting zones